Clinical trials in critical care: can a Bayesian approach enhance clinical and scientific decision making?. Issue 2 (February 2021) - Yarnell, Christopher J; Abrams, Darryl; Baldwin, Matthew R; Brodie, Daniel; Fan, Eddy; Ferguson, Niall D; Hua, May; Madahar, Purnema; McAuley, Danny F; Munshi, Laveena; Perkins, Gavin D; Rubenfeld, Gordon; et al.
Summary: Recent Bayesian reanalyses of prominent trials in critical illness have generated controversy by contradicting the initial conclusions based on conventional frequentist analyses. Many clinicians might be sceptical that Bayesian analysis, a philosophical and statistical approach that combines prior beliefs with data to generate probabilities, provides more useful information about clinical trials than the frequentist approach. In this Personal View, we introduce clinicians to the rationale, process, and interpretation of Bayesian analysis through a systematic review and reanalysis of interventional trials in critical illness. In the majority of cases, Bayesian and frequentist analyses agreed. In the remainder, Bayesian analysis identified interventions where benefit was probable despite the absence of statistical significance, where interpretation depended substantially on choice of prior distribution, and where benefit was improbable despite statistical significance. Bayesian analysis in critical care medicine can help to distinguish harm from uncertainty and establish the probability of clinically important benefit for clinicians, policy makers, and patients.